Aplikasi Teknik Evaluasi pada Pembelajaran Akidah-Akhlak di Madrasah Aliyah Negri - Herman Yunianto; Nanang Nuryanta (EL-TARBAWI, 2020)
The limited opportunity for teachers to apply evaluation on akidah akhlak subject in madrasah is one of the reasons this research was conducted. This study aims to determine the implementation of cognitive, affective, and psychomotor evaluation techniques on akidah akhlak subject s for class XI of the Religious Program in MAN 3 Sleman. This research use a qualitative approach; purposive and snowball sampling for determining data sources; observations, interviews, and documentation for collecting data; triangulation of sources, techniques, and time for testing the validity of the data; as well as data reduction, display data and conclusions drawing for analyzing data. The results showed that the techniques used in the evaluation of akidah akhlak subject were: (a) cognitive aspects including: written tests, oral tests, and assignments using multiple choice assessment instruments and descriptions, (b) the affective aspect uses observation techniques using a Likert scale, thrustone, guttman, and interest measurement, and (c) psychomotor aspects include: practical techniques and portfolios.